Heterosis estimates in F2 diallel population of spring wheat at two different cultural conditions (Bangladesh Journal of Agricultural Research, 2010)
Spring wheat (Triticum aestivum L.) varieties Gaurab, Kanchan, Balaka, Sonora, Protiva, Pavon, and Anza were used as parent materials to estimate heterosis in a set of 7 × 7 diallel crosses. The diallel trial was carried out for seven parental material and their 21 F2 progenies under two contrasting cultural conditions for different yield and yield contributing characters. Cultural conditions I is provided by the BARI recommended doses of fertilizer and irrigation, and 2 have no fertilizer but two irrigations once at crown root initiation stage and twice at panicle initiation stage. Heterosis was measured as i) Relative heterosis and ii) Heterobeltiosis. The result of relative heterosis revealed cross Sonora × Anza exhibited superior performance for grain yield/plot in environment-i. Desirable negative heterosis was observed in cross Balaka × Anza in environment-I and Pavon x Anza in environment-2 for days to 50% heading character. For days to maturity, desirable negative heterosis was found in cross Pavon x Anza in both cultural environments. Estimate of heterobeltiosis for different yield contributing characters showed that cross Sonora x Anza exhibited highest heterosis for grain yield/plant in environment-1 and Kanchan x Balaka in environment-2. Cross Pavon x Anza exhibited superior relative heterosis and heterobeltiosis for 100-grain weight in both cultural environments. By comparing two cultural conditions, it was found that 1 is better than 2 for all the characters. Keywords: Relative heterosis; heterobeltiosis; spring wheat; F2 generation; GxE interaction. DOI: 10.3329/bjar.v35i3.6448Bangladesh J. Agril. Res. 35(3) : 413-422